Chronic recurrent multifocal osteomyelitis: a case report - Maria Francesca Gicchino; Mario Diplomatico; Carmela Granato; Daniela Capalbo; Pierluigi Marzuillo; Alma Nunzia Olivieri; Emanuele Miraglia del Giudice (BMC, 2018)
Abstract Background Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic nonbacterial osteomyelitis, is a rare, noninfectious inflammatory disorder that causes multifocal bone lesions with swelling and pain. Lytic and sclerotic bone lesions could be found on X-ray. Short tau inversion recovery magnetic resonance imaging (STIR MRI) shows bone marrow oedema, bone expansion, lytic areas and periosteal reaction. CRMO is characterized by periodic exacerbations and remissions of unclear/unknown pathogenesis. Case presentation A 10 years old girl, suffering from pain in her right shoulder since the age of 9 years presented to our Department. Thanks to clinical data, laboratoristic and radiological findings and bone biopsy CRMO was diagnosed. So patient started anti-inflammatory treatment and her conditions improved. Conclusions In a child with bone pain should be considered also rare condition as CRMO to perform a correct diagnosis and start an adequate treatment avoiding complications such as bone damage. This condition should be suspected in a child with recurrent bone pain, modest increase of inflammatory indices, lytic or sclerotic bone lesion on X Ray. Typical CRMO localizations are metaphyses of long bones, pelvis, clavicle, vertebral column, sternum, ribs, jaw, but any bone can be involved. The most common CRMO differential diagnosis is represented by infections, malignant bone tumors, Langerhans Cells Histiocytosis (LCH).